Distributed Engineering Environment for the Design of Electronic Systems - Schattkowsky, Tim; Müller, Wolfgang (Proceedings of CCE'03)
Computer supported collaborative work (CSCW) is currently of growing interest for application industrial context. Integrated workflow systems are available to allow the integration of globally distributed teams. However, in many areas (i.e. in electronic design automation), tool integration remains to be a critical issue since existing legacy tools have to be integrated into distributed workflows. By integrating tools based on the operational semantics, dynamic assignment and replacement of tools in the workflows becomes possible. We present a middleware for secure collaborative engineering that enables flexible tool management and overcomes existing networking problems through a peer-to-peer based network infrastructure.